Influence of Selenium Element on Regeneration and Fecundity of the Riverine crab Sesarma boulengeri Calman - Sultan, E. N.; AL-Adub, A. H. Y.; Awad, N. A. N. (Iraqi Journal of Aquaculture, 2022)
The study of the influence of selenium on the regeneration and fecundity of the crab Sesarma boulengeri Calman has been conducted. The results demonstrated: The effect of selenium on the regeneration of walking legs of S. boulengeri Calman. Morphology of the regenerated appendage was different from control specimen. The speed of growth in the regenerated bud was lower than the control and it was depended on the size class of the crab. Regeneration index (R) was higher in the small crabs than in the large ones and in single autotomy than in double autotomy. Fecundity varied, when females exposed to selenium (0.27, 1.35, 2.7 ppm). It showed a decrease with all stages, especially in the first and second stage. The eggs in the last stage suffered more teratogens with exposure time and the concentration of selenium. 3